COMPARATIVE STUDY OF INVERTING SUTURELINE VERSUS OVER AND OVER CONTINUOUS SUTURING IN HYPOSPADIAS REPAIR - Khan, Basharat Ali; Shah, Muhammad Ali; Khan, Faraz Basharat (Journal of Ayub Medical College Abbottabad, 2009)
Background: Hypospadias is one of the most common congenital anomalies of the male newborns affecting 1 in 300. Urethral meatus lies ectopically on the ventral surface of penis proximal to its normal position. There is defective development of urethral spongiosum and ventral prepuce. Various degrees of chordee may be associated. Objective of the study was to study the incidence of urethrocutaneous fistula formation after hypospadias repair employing two different suturing techniques. This Prospective Randomised Descriptive Clinical Trial was conducted in Department of Surgery, Fauji Foundation Hospital, Rawalpindi and Basharat Hospital, Rawalpindi, during a period of five years from January 2005 till December, 2009. Methods: A prospective study of 100 patients of glanular/penile hypospadias requiring repair was completed from January, 2005 till December, 2009. Fifty of these patients had urethral tube reconstruction using conventional over and over continuous suturing technique (Group-1). In another group of fifty patients continuous inverting sutures (Connel technique) commonly used in intestinal anastomosis was employed (Group-2). Polyglycolic acid sutures 4/0 to 6/0 as appropriate were used for all the repairs in both the groups by the same surgeon. Results: Six (12%) urethrocutaneous fistulas formed in the Group-1 of fifty patients with over and over continuous suturing as compared to 4 (8%) in Group- II with equal number of patients where inverting suture technique was used. Conclusion: Inverting sutures reduce the incidence of urethrocutaneous fistula formation in hypospadias repair. Keywords: hypospadias, urethroplasty, urethrocutaneous fistula